Money, it's a gas : análise da eficiência dos gastos de campanha no Brasil - Suzana Alves da Silva (2023)
This thesis investigates whether campaign spending by candidates for federal deputy in Brazil in the 2018 elections is efficient. Therefore, it is descriptive and exploratory research. To this end, we applied data envelopment analysis (DEA) to measure the relative efficiency between candidates for federal deputy in the 2018 elections. The first chapter is a theoretical chapter that deals with money, voting and financing of electoral campaigns, we analyze the influence that money has in elections and consequently in voting, in addition to the rules regarding campaign financing. In the second chapter, we analyze the relative efficiency of campaign spending by candidates for federal deputy in Brazil in 2018, using the variable return to scale and input orientation model developed by Banker, Charnes and Cooper (1984).Where we show that the majority of candidates considered benchmarks have total expenses much lower than the candidates who were elected, but who were not efficient. Finally, in the third and final chapter, we explore the factors that are associated with the efficiency of campaign spending in Brazil. Five variables are explored in the chapter, ideology, incumbent, type of spending, government coalition and finally the party variable. We used linear regression to measure the association between variables. The last chapter shows us that local politics is still important. There was a low association between types of spending and efficiency, but the variable that showed the greatest association with campaign spending efficiency was the party ideology variable, although others were also associated.